Experimental and Numerical Studies of Structured Packing Column - Sun, Biao; Tade, Moses; Bhatelia, Tejas; Utikar, Ranjeet; Letizia, Nathan; Evans, Geoffrey; Pareek, Vishnu (2018)
This study investigated the hydrodynamic performance of two different existing structured packings, namely Mellapak 250Y and Montzpak B1-500. Two different-sized packing columns, i.e. 200mm diameter and 54mm diameter, were used. As the commercial structured packings were not available for small lab-scale dimensions, the replicas were manufactured additively using 3D printing. To measure the liquid distribution for counter-current flow of air and water, the Wire Mesh Sensor (WMS) was used at the location of packing transitions. Computational fluid dynamics (CFD) simulations were carried out to better understand the packing performance, e.g. pressure drop along the column height, liquid film holdups and liquid distributions. A good agreement was achieved between experimental data and simulation results. The methodology and results discussed in this study can provide indepth insights into the performance of the commercial packings and be of importance when testing new packings.